L34 Caregiver Supports For Families Of Those With Huntington's Disease. (17th September 2014) - Ennis, A; Gallagher, A; Hoblyn, J
Abstract : Background: Families with Huntington's disease (HD) face complex social, economic and legal issues. Stigmatisation is an ongoing problem as HD is not well understood generally and lack of accurate information can, and often does, result in discrimination. Loss of employment and income is a major problem as is loss of role and sense of identity. The State services are limited and there is poor access to specialist services such as neuropsychiatry, neurology, and an absence of adequate home support services. Of particular concern is the issues around life insurance and mortgage approval. All these issues are superimposed on families who are facing life with an illness that is progressive and life limiting. Case histories: We hold regular multidisciplinary team meetings with our six long term care patients and their families, also offering individual support to family members and family therapy. Often family members were under stress caring for their own young families and their potential for developing HD. Attention to financial stressors was paramount. We are currently developing education programmes for family members and recovery focused programmes for those who are recently diagnosed and their nominated family members. Conclusions: Engaging family members can be challenging and also must be approached with sensitivity as individual family members are at different stages of acceptance (especially if they are positive for HD) and may not have the capacity to engage - though this can change over time. It is essential that we work closely with the Huntingtons Disease Association of Ireland (HDAI).